And now for something completely different—new names in Clinopodium with comments on some types - Bräuchler, Christian (Phytotaxa, 2018)
New combinations are proposed in Old World Clinopodium replacing the names currently in use for the following taxa: C. album for “C. thymifolium”, C. brevifolium for C. insulare, C. italicum for Micromeria marifolia var. italica. Clinopodium × hostii is proposed as the correct name for Clinomicromeria × hostii. Notes on typification for several other taxa are provided.